Model Pemberdayaan LPD Bermasalah di Provinsi Bali - I Ketut Yadnyana; Sudarsana Arka; Ni Wayan Alit Erlina Wati (Juara: Jurnal Riset Akuntansi, 2022)
This research aims to create strategies and models as guidelines for empowering problematic LPD related to aspects of human resources, institutions, businesses, capital, and business cooperation networks. The population is all problematic LPDs in Bali Province. Based on the Krejcie table, the number of samples for a population of 181 is determined to be at least 123. The source of data is primary data obtained by distributing questionnaires. Based on the human resources aspect, the strategy to solve problematic LPDs is to increase the knowledge and skills of human resources through education and training. It needs business cooperation networks and strengthening government support from the institutional aspect. From the business aspect, it is to strengthen the support of adat village manners by regenerating the trust that once faded. The capital aspect increases awareness of adat village manners regarding the business capital requirements. From the aspect of business cooperation networks, it is the pioneering and strengthening of cooperation networks by utilizing the potential of adat village manners, government facilities, and related agencies. Meanwhile, the empowerment model is applied through education, apprenticeship, comparative studies, facilities, and the creation of a conducive climate.